Role of the Mosaic Cisternal Maturation Machinery in Glycan Synthesis and Oncogenesis - Sahu, P.; Balakrishnan, A.; Di Martino, R.; Luini, A.; Russo, D. (Frontiers in Cell and Developmental Biology, 2022)
Tumorigenesis is associated with the deregulation of multiple processes, among which the glycosylation of lipids and proteins is one of the most extensively affected. However, in most cases, it remains unclear whether aberrant glycosylation is a cause, a link in the pathogenetic chain, or a mere consequence of tumorigenesis. In other cases, instead, studies have shown that aberrant glycans can promote oncogenesis. To comprehend how aberrant glycans are generated it is necessary to clarify the underlying mechanisms of glycan synthesis at the Golgi apparatus, which are still poorly understood. Important factors that determine the glycosylation potential of the Golgi apparatus are the levels and intra-Golgi localization of the glycosylation enzymes. These factors are regulated by the process of cisternal maturation which transports the cargoes through the Golgi apparatus while retaining the glycosylation enzymes in the organelle. This mechanism has till now been considered a single, house-keeping and constitutive function. Instead, we here propose that it is a mosaic of pathways, each controlling specific set of functionally related glycosylation enzymes. This changes the conception of cisternal maturation from a constitutive to a highly regulated function. In this new light, we discuss potential new groups oncogenes among the cisternal maturation machinery that can contribute to aberrant glycosylation observed in cancer cells. Further, we also discuss the prospects of novel anticancer treatments targeting the intra-Golgi trafficking process, particularly the cisternal maturation mechanism, to control/inhibit the production of pro-tumorigenic glycans.